Quantifying Dutch disease effects and asymmetry in economic responses to oil price volatility in Kuwait - Manal Shehabi (The Oxford Institute for Energy Studies, 2020)
The motivation for this study is to fill existing gaps in the understanding of the economic impacts of oil price volatility on Gulf Cooperation Council (GCC) economies and to assist in the management of recent oil price shocks following the COVID-19 pandemic. To that end, this paper employs an economy-wide general equilibrium model that embodies Kuwait's economic structure and accounts for its political and economic constraints to quantify asymmetric responses of terms of trade shocks in Kuwait. It highlights impacts on non-energy sectors and `second-best effects' to draw potentially-applicable lessons for the GCC. The results show that, consistent with expectations in the literature, there is potentially an asymmetric response between equi-proportional terms of trade shocks; yet in the current economic policy environment, this asymmetry is either non-existent for some economic variables or very limited and is significantly smaller than the asymmetry shown to exist in other resource-dependent and specialized economies. The potential asymmetry is mitigated by idiosyncratic adjustment mechanisms, namely the sovereign wealth funds (SWFs) and expatriate labour movement, especially when oligopolies are regulated. Contrary to theory expectations, the results also show there is a weak and limited (reverse) Dutch disease dynamic: specifically, there is a strong resource movement effect of the Dutch disease in Kuwait but an almost non-existent de-industrialization effect. Booms expand mainly nontraded oligopolies' markup along with the energy sector and the SWFs, and raise rent distribution payments to the public. Busts reduce distribution payments and markups of oligopolistic firms, but the latter do not expand into the export market despite the depreciating real exchange rate. The regulation of oligopolies reduces rent-seeking behaviour and renders the economy more open and efficient at managing both high and low oil prices. The economic story behind these dynamics is that economic efficiency is largely reduced due to a high concentration of oligopolies in the public energy, as well as in the private non-energy, sectors; these oligopolies capture terms of trade shocks' rents that detract from growth-enhancing innovation, hampering economic efficiency, competitiveness, and growth. Oligopolistic behaviour is enabled by (a) access to government subsidies; (b) access to expatriate labour whose wages are lower than those of national labour, have flexible contracts, and are therefore able to enter or exit the market with little cost to firms or repercussions to unemployment; (c) limited regulation; and (d) limited incentive to regulation because SWFs have been set up as quasi-industries, offering the government an alternative to industrial expansion and economic diversification. The sterilization of oil revenue through the SWF reduces available investments, further eroding potential reverse Dutch disease dynamics. The implication of this is that Dutch disease during high oil price episodes is not inevitable, but a result of policy choice, the downside of which is that reverse Dutch disease effects remain weak. There are important policy implications from this study which indicate that, even with oil price recovery, GCC's existing economic policy regimes and procyclical fiscal management of oil rents are unsustainable and cannot produce the stated desired economic diversification. Although politically difficult, industrial regulation is a potential path in the GCC's transformation plans to raise economic efficiency, manage oil and non-oil rents, expand non-energy sectors, and enhance economic resiliency in light of continuous oil price volatility.
Keywords: 330; asymmetry; CGE; Dutch disease; energy; expatriate labour; general equilibrium; Gulf; International Trade; Kuwait; MEP 24; MEP24; Middle East; oil price; Oligopoly; Regulation